Aplikasi Transparansi Dana Donasi Untuk Anak Yatim Piatu Berbasis Web - Imas Maslekha; Riyanto Mustolih; Dedih Dedih (LPPM STMIK Rosma, 2018)
Orphanages get operational funds from donors. However, the form of aid expenditure has not been managed transparently and reported to all donors. For that we need an application transparasi donation fund orphans based online so as to facilitate the Foundation in accounting for the activities of donation funds and donors can easily access the report when needed